Analisis Pertumbuhan Penduduk Kabupaten Kepulauan Yapen dan Penentuan Metode Penaksiran yang Relevan - Pieter Noisirifan De Fretes; Waspada Meliala (Journal on Education, 2023)
The aims of this study are: To find out the population growth trend of Yapen Islands district during the 2012-2020 period if the development pattern is assumed to be linear, the population growth trend models of Yapen Islands district during the 2012-2020 period if the growth pattern is assumed to be non-linear, the most relevant estimation model in estimating the population of the Yapen Islands district in the future, an analytical tool; Linear Trend Analysis, Non-Linear Trend Analysis and Determination of Relevant Forecasting Methods. Results of analysis: The average population of Yapen Islands Regency during the observation period is approximately 96,240 people per year; while the data movement pattern shows a trend or tendency to increase linearly with an estimated average increase of 3,828 people per year. The application of the four Non-Linear Trend models produces model parameters that indicate a trend of increasing the population of Yapen Islands Regency from year to year with a movement pattern non-constant data. The use of the Least Squares Method produces a total value of the least squared difference in the Exponential Trend model with an average difference of only around 365 people per year. This indicates that the Exponential Trend is the most relevant method used for estimation and forecasting.